COMPARATIVE ANALYSIS OF THE IMPACT OF DIE DESIGN ON ITS LOAD AND DISTRIBUTION OF STRESS DURING EXTRUSION - NOWOTYŃSKA, Irena; KUT, Stanisław (Applied Computer Science, 2018)
In the paper a numerical comparative analysis of stresses in a steel die compressed by a ring during the extrusion process was presented. In the research, three design solutions of the die were used. The solutions vary depending on the quotient of the wall thickness of the die insert and the wall thickness of the compression ring while maintaining a constant tool diameter. The stresses occurring in the areas of the ring and the die were calculated depending on the design version of the tool and the pressure value. The analysis was carried out for the quotients of the die wall thickness to the ring wall thickness of 0.57, 1 and 1.75 and three press-in values of 0.004, 0.008 and 0.016 mm. The conducted research allowed determining the impact of the die design and assembly interference on the load bearing capacity. It was discovered that the use of a die insert with a smaller thickness compared to the thickness of the compression ring was the most advantageous from the point of view of the circumferential stresses.